Functional and Structural Characterization of Neutralizing Epitopes of Measles Virus Hemagglutinin Protein - Tahara, Maino (American Society for Microbiology, 2013)
Effective vaccination programs have dramatically reduced the number of measles-related deaths globally. Although all the available data suggest that measles eradication is biologically feasible, a structural and biochemical basis for the single serotype nature of measles virus (MV) remains to be provided. The hemagglutinin (H) protein, which binds to two discrete proteinaceous receptors, is the major neutralizing target. Monoclonal antibodies (MAbs) recognizing distinct epitopes on the H protein were characterized using recombinant MVs encoding the H gene from different MV genotypes. The effects of various mutations on neutralization by MAbs and virus fitness were also analyzed, identifying the location of five epitopes on the H protein structure. Our data in the present study demonstrated that the H protein of MV possesses at least two conserved effective neutralizing epitopes. One, which is a previously recognized epitope, is located near the receptor-binding site (RBS), and thus MAbs that recognize this epitope blocked the receptor binding of the H protein, whereas the other epitope is located at the position distant from the RBS. Thus, a MAb that recognizes this epitope did not inhibit the receptor binding of the H protein, rather interfered with the hemagglutinin-fusion (H-F) interaction. This epitope was suggested to play a key role for formation of a higher order of an H-F protein oligomeric structure. Our data also identified one nonconserved effective neutralizing epitope. The epitope has been masked by an N-linked sugar modification in some genotype MV strains. These data would contribute to our understanding of the antigenicity of MV and support the global elimination program of measles.